Optimal Rescheduling of Distributed Energy Resources Managed by an Aggregator - Spínola, João (2021)
Distributed energy resources integration into energy markets and power systems operation has been one of the main concerns of operators and other entities, mainly because of the recent growth and the features that these resources can provide. The need for managing tools that provide solutions to these concerns is evident, and can be addressed through several ways. The present paper proposes a model for the integration of distributed energy resources into power systems operation using an aggregator. The management considers the aggregator’s perspective, and therefore, the objective is to minimize the costs of system balance. For this, it is proposed a re-scheduling of resources, i.e. after a first scheduling with individual prices the resources are clustered, and for each group, a tariff is defined and applied to each of the resources that belong to it, being then scheduled again considering the new group tariffs.